Kesejahteraan Masyarakat Jakarta 1969-1997 - Winario; Abrar; Sri Martini (CHRONOLOGIA, 2024)
The welfare of the people of Jakarta during the period of governor Ali Sadikin to Surjadi Soedirdja showed certain developments. This study aims to determine the welfare development of the DKI Jakarta government during the tenure of Ali Sadikin to Surjadi Soedirdja's term. This study uses the historical method which consists of 5 stages including topic selection, source gathering (heuristics), source criticism (verification), interpretation (interpretation), and writing (historiography). The findings of the researchers are aimed at increasing the welfare of Jakarta in various fields. The health sector has increased, especially the availability of 99 hospitals and the development of 442 health centers, the availability of 15,227 treatment rooms. And the female population who use contraception is 317,896 out of the female population of 3,694,971. The Education Sector has had development results with many school buildings having been built as many as 6,924 schools as well as many educators 88,710 and students as many as 1,654,041. The development of the existing workforce in Jakarta is 3,646,285 and is dominated by working in labour-intensive fields. House construction in Jakarta has reached an area of 44,462.208 ha. Social security that the Provincial Government implements by guaranteeing that various welfare support facilities are properly available.The welfare of the people of Jakarta during the period of governor Ali Sadikin to Surjadi Soedirdja showed certain developments. This study aims to determine the welfare development of the DKI Jakarta government during the tenure of Ali Sadikin to Surjadi Soedirdja's term. This study uses the historical method which consists of 5 stages including topic selection, source gathering (heuristics), source criticism (verification), interpretation (interpretation), and writing (historiography). The findings of the researchers are aimed at increasing the welfare of Jakarta in various fields. The health sector has increased, especially the availability of 99 hospitals and the development of 442 health centers, the availability of 15,227 treatment rooms. And the female population who use contraception is 317,896 out of the female population of 3,694,971. The Education Sector has had development results with many school buildings having been built as many as 6,924 schools as well as many educators 88,710 and students as many as 1,654,041. The development of the existing workforce in Jakarta is 3,646,285 and is dominated by working in labour-intensive fields. House construction in Jakarta has reached an area of 44,462.208 ha. Social security that the Provincial Government implements by guaranteeing that various welfare support facilities are properly available.